The Effect of Vitamin D Deficiency on Anemia in Children and Adolescents: Meta-Analysis - Dianika, Bani; Dewi, Yulia Lanti Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Anemia in children and adolescents has an impact on central nervous system damage that can continue into adulthood. Some evidence states that one of the causes of anemia is vitamin D deficiency. This study aims to estimate the magnitude of the effect of vitamin D deficiency on the incidence of anemia in children and adolescents, through a meta-analysis of primary studies conducted by previous authors. Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: children and adolescents, intervention: vitamin D deficiency, comparison: no vitamin D deficiency, outcome: anemia. The articles used in this study were obtained from three databases, namely PubMed, Google Scholar, and Science Direct, using the search key